Automação residencial utilizando microcontrolador Arduino e aplicativo móvel - Vendrametto, Marlon Bruno (2018)
This work aims to apply the concept of Internet of Things in a residence, allowing the control of the resources through a mobile application. Firstly, explain the functions of ESP12E module and communication with sensors. The module has a microcontroller and its operation seems with the Arduino tools, but with the ability to exchange information with a wireless network. This communication occurs when the mobile application send requests to the server, that transmits to ESP12E, and through the armazenated code in C language in your memory, analise the instructions inside of conditions fixed and send eletric signals to the sensors or actuators that be conected and help to control. First, implementing control of an LED that turns on or off and represents control of a residence light. Thereafter, an ultrasound sensor and a siren that emits an audible alert when an intruder's presence is verified and thus represents an alarm system. Finally, a servo motor actuator that opens and closes a door. All features can be manipulated by touch in the smartphone screen, which is built in a cross-platform language, based on the Ionic framework that enables the development of one code capable of running in parallel on two different systems, Android and iOS. This research allows the reader to apply the concept of residential automation and maintain the expansion of it, improving data control to ensure economic and family sustainability.